Pengembangan Media Puzzle pada Mata Pelajaran Fikih Materi Sholat Fardu di MTs Al-Inayah Manado - Nur Fadli Utomo; Mutmainah Mutmainah; Indah Prayudhisty Mamonto (IAIN Manado, 2022)
Development of Puzzle Media in the Fiqh Subject of Fardu Prayer Material at MTs Al-Inayah Manado. This study aims to produce puzzle media products in the fiqh subject of fardu prayer material and test the feasibility of these products to support learning in class VII MTs Al-Inayah Manado. The development model used is Sugiyono's level 1 development model which has 5 stages, namely potentials and problems, literature study or information gathering, product design, design validation, and tested design. Data collection techniques used in this study were questionnaires, observation, and documentation. The questionnaire was addressed to the media validator and material validator. The subjects of this research trial were educators and class VII students of MTs Al-Inayah Manado, totaling 30 students. The measurement scale used is the Likert scale. The results of the Likert scale measurements, then look for the percentage of a number of sample subjects.The results of this study indicate that this puzzle is suitable for use as teaching material, this is based on scores obtained through assessments from material experts getting a percentage of 87% with very valid criteria, and an assessment score from media experts getting a percentage of 77.33% with valid criteria. In product trials on students, it was found that the percentage of feasibility of puzzle media was 91.6% with very valid criteria. And the response from educators gets a percentage of 85.33% with very valid criteria. Based on the results of expert validation and product trials, the authors can conclude that puzzle media is very suitable for use as teaching material